Next generation energy performance assessment methods for EPCs using measured energy data - Verheyen, Jan; Lambie, Evi; Fernández Boneta, María; Maia, Iná; Kranzl, Lukas; Urbanz, Theresa; Frick, David (CLIMA 2022 conference, 2022)
The European Union (EU) aims at net-zero greenhouse gas emissions by 2050, with intermediate quantified targets in 2030. To achieve these long-term objectives, the renovation rates in the building sector should be increased. Therefore, as part of the European Green Deal, the EU has initiated the renovation wave initiative with the ambition to at least double the annual renovation rate and to foster deep renovation. An important tool to raise awareness regarding the building energy performance and the need for renovation is the energy performance of buildings certification (EPC). The EPC was already introduced in the Energy Performance of Buildings Directive (EPBD) in 2002 (2002/91/EC) and is a specific focus of the upcoming revision of the EPBD. Currently, EPCs are mostly based on calculation of theoretical performance. Despite challenges such as correction for actual occupant behaviour and weather conditions, the inclusion of measured data of building energy use may lead to additional benefits, improve the quality, reliability and usability of next-generation EPCs. On the one hand, energy performance indicated based on actual energy use data relates better with non-experts understanding of energy consumption and bills. On the other hand, the actual energy use data can attribute to a more efficient and accurate reflection of the actual energy performance of a building. Such aspects are important for augmenting user acceptance and increasing trust in the market, which in turn may lever renovation rates. This paper presents energy performance indicators based on measured building energy use, either to replace or to supplement EPC indicators currently in use. First, state of the art approaches for energy performance evaluation based on data of measured energy use or related parameters are described. Next, implementation cases are presented that are being developed in the frame of EU H2020 research projects ePANACEA and X-Tendo. Finally, the outline of future work within these projects is given.